The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fmed.2021.783178
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraocular Cytokine Levels of Choroidal Neovascularization Secondary to Different Retinopathies

Abstract: Purpose: To investigate and compare the aqueous concentrations of vascular endothelial growth factor (VEGF) and other inflammatory cytokines in various choroidal neovascularization (CNV) diseases and types.Methods: This observational study included 127 naive eyes with CNV and 43 control eyes with cataracts. Aqueous humor (AH) samples were obtained prior to intravitreal anti-VEGF injection or cataract surgery. Multiple inflammatory cytokines, including VEGF, interleukin (IL) 6, IL-8, IL-10, interferon-inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…In the mCNV group, the AH concentration and vitreous mass of cytokines had no correlation with CMT or size of CNV. The possible explanations are as follows: In other CNV diseases, such as AMD, type 1 CNV did not affect visual activity in the early stages and patients seek medical attention later, when the size of CNV was large and VEGF level were significantly elevated ( 11 ). In contrast, the majority of mCNV are type 2 CNV, which rapidly affected vision as soon as it appeared.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the mCNV group, the AH concentration and vitreous mass of cytokines had no correlation with CMT or size of CNV. The possible explanations are as follows: In other CNV diseases, such as AMD, type 1 CNV did not affect visual activity in the early stages and patients seek medical attention later, when the size of CNV was large and VEGF level were significantly elevated ( 11 ). In contrast, the majority of mCNV are type 2 CNV, which rapidly affected vision as soon as it appeared.…”
Section: Discussionmentioning
confidence: 99%
“…We defined the central macular thickness as the average retinal thickness within the 1-mm diameter central field of the Early Treatment Diabetic Retinopathy Study. The optical coherence tomography angiography (OCTA) images were produced using a split-spectrum amplitude decorrelation angiography (SD-OCT) equipment (RTVue-XR Avanti; Optovue, Inc, Fremont, CA).Then the size of CNVs was marked with the manual selection tools and calculated based on the built-in software ( 11 ). Images with poor quality (quality <7) were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that the proangiogenic cytokine VEGF levels were distinctly upregulated in the CSC group than in the control group. Liu et al have reported that the AH concentration of VEGF was signi cantly higher in various CNV diseases including CSC [14] . However, there was evidence that aqueous or plasma VEGF levels in patients with acute or chronic CSC were downregulated compared with the controls [15,16] .…”
Section: Discussionmentioning
confidence: 99%